2019
DOI: 10.1111/1460-6984.12467
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers navigating rehabilitative care for people with aphasia after stroke: a multi‐lens perspective

Abstract: Background Up to 40% of stroke survivors acquire aphasia and require long‐term caregiver assistance after discharge from the hospital. Caregivers assume multiple roles as they help people with aphasia to access outpatient rehabilitative care in an increasingly person‐centred model of care. Examining caregiver roles and how different stakeholders in the rehabilitative journey perceive these roles may be the first step in providing more tailored support to caregivers and improving outcomes for both caregivers an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…We believe these letters complement her interview account and we argue that it is appropriate to revisit this data and share this story despite the time that has elapsed since the data was collected. This is not only because Rhona requested that we do so, but also because, as demonstrated in the introductory review, the issues of inadequate information, poor communication, and exclusion from discharge planning raised in this narrative remain current, both in Australia and beyond (Rose et al, 2019 ; Shafer et al, 2019 ). In addition, the combination of these two sources of data is valuable, and the letters offer an unusual opportunity to explore these issues in a novel way.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We believe these letters complement her interview account and we argue that it is appropriate to revisit this data and share this story despite the time that has elapsed since the data was collected. This is not only because Rhona requested that we do so, but also because, as demonstrated in the introductory review, the issues of inadequate information, poor communication, and exclusion from discharge planning raised in this narrative remain current, both in Australia and beyond (Rose et al, 2019 ; Shafer et al, 2019 ). In addition, the combination of these two sources of data is valuable, and the letters offer an unusual opportunity to explore these issues in a novel way.…”
Section: Methodsmentioning
confidence: 99%
“…Avent et al (2005) suggested that many family members of people with aphasia felt "so overwhelmed, you don't know what you need" (p. 371) and did not even know what questions to ask. Shafer et al (2019) included seven family carers of people with aphasia in their study. They found:…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could also escalate the hospital admission rates and diminish the bed capacity for emergency cases. Inadequate resources as alluded to earlier on leads to frustration of the Caregivers and subsequent poor care delivery (Shafer, Shafer, & Haley, 2019). The research participants reported lack of resources to support the informal HBP caregivers.…”
Section: Discussionmentioning
confidence: 91%